Performance Management of Special Fund for Sports Industry Development in Jiangsu Province - Yang Wen; Xu Chen; Tianyi Gu; Fangliang Yu (Complexity)
In 2011, Jiangsu Province set up the guidance fund for sports industry. In 2016, Jiangsu Provincial Finance Department jointly issued the document with Jiangsu Provincial Sports Bureau, which was changed to “Jiangsu Special Fund for Sports Industry Development.” By 2019, Jiangsu Province has funded 1,009 sports industry development projects with a total investment of 796.6 million yuan. The effect of the investment has attracted extensive attention from the government, society, and enterprises. Entrusted by Jiangsu Sports Industry Guidance Center, this research team spent one year on the performance research of 1,009 projects supported by special funds for the development of sports industry, from the construction of evaluation index system to the design, issuance, collection, and processing of questionnaires. Using the methods of literature, questionnaire, expert interview, and mathematical statistics, this paper takes the performance management of the special funds for the development of sports industry in Jiangsu Province as the research object, based on the investigation and analysis of the current situation of the special funds for the development of sports industry in Jiangsu Province. It analyzes the special funds from four aspects: the rate of funds in place, the ratio of funds pulled, the completion rate of project implementation, and the rate of fund prerecovery. Then, this paper expounds the current situation, effectiveness, and problems of the performance management of the special funds for the development of sports industry and puts forward some countermeasures and suggestions for improvement.